Marketings, creating value for customers / Gilbert A. Churchill, J. Paul Peter - Churchill Jr, Gilbert A. [et.al] (1995)
The marketing environment, meeting social and ethical standars in marketing, marketing in a global environment; stategic marketing planning, creatin a marketing plan, implementan and controlling the marketing effort, marketing research, information and techology consumer behavior; organizational buying behavior, market segmentation, new product, existing products, services, fundamentals of pricing, pricin goods and services, managing distribution channels, wholesaling, retailing, and physical distribution, the communications mix, advertising, sales promotion, and publicity, fundamentals of pricing, pricing goods and services, managing distribuition channels, wholesaling, retailing, ad physical distribution, the communications mix, advertising, sales promotion, and publicity, personal salling and sales management.